Metal-organic framework (MOF) integrated Ti3C2 MXene composites for CO2 reduction and hydrogen production applications: a review on recent advances and future perspectives - Tahir, Beenish; Alraeesi, Abdulrahman; Tahir, Muhammad (Frontiers in Chemistry, 2024)
Titanium carbide (Ti3C2) MXenes due to their structural and optical characteristics rapidly emerged as the preferred material, particularly in catalysis and energy applications. On the other hand, because of its enormous surface/volume ratio and porosity, Metal-organic Frameworks (MOFs) show promise in several areas, including catalysis, delivery, and storage.The potential to increase the applicability of these magic compounds might be achieved by taking advantage of the inherent flexibility in design and synthesis, and optical characteristics of MXenes. Thus, coupling MOF with Ti3C2 MXenes to construct hybrid composites is considered promising in a variety of applications, including energy conversion and storage. This paper presents a systematic discussion of current developments in Ti3C2 MXenes/MOF composites for photocatalytic reduction of CO2, and production of hydrogen through water splitting. Initially, the overview and characteristics of MXenes and MOFs are independently discussed and then a detailed investigation of efficiency enhancement is examined. Different strategies such as engineering aspects, construction of binary and ternary composites and their efficiency enhancement mechanism are deliberated. Finally, different strategies to explore further in various other applications are suggested. Although Ti3C2 MXenes/MOF compositeshave not yet been thoroughly investigated, they are potential photocatalysts for the production of solar fuel and ought to be looked into further for a range of applications.